1986
DOI: 10.1007/bf00422736
|View full text |Cite
|
Sign up to set email alerts
|

Blood platelet activation and increase in thrombin activity following a marathon race

Abstract: To see whether strenuous prolonged exertion increases blood platelet activation and thrombin activity in healthy well-trained men, 16 male amateur runners (mean age 31,8) were studied. A marathon race (mean time 2 h 44 min 30 s) caused a significant increase in plasma beta-thromboglobulin (beta-TG), platelet factor 4 (PF4), fibrinopetide A (FPA) and factor VIII (F VIII) activity. Sixty min after exertion beta-TG and F VIII activity were still significantly elevated. FPA continued to rise, reaching peak values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
39
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 36 publications
8
39
1
1
Order By: Relevance
“…All blood samples were taking with subjects lying down in order to rule out orthostatic changes in plasma volume (18). The results of authors with comparable collectives and methods to ours (11,13,15,16) confirm our measurements of changes in plasma volume. Previous studies had not reported a positive correlation of the plasma volume increase from 3 to 34 hr post marathon with the runners' years of training.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…All blood samples were taking with subjects lying down in order to rule out orthostatic changes in plasma volume (18). The results of authors with comparable collectives and methods to ours (11,13,15,16) confirm our measurements of changes in plasma volume. Previous studies had not reported a positive correlation of the plasma volume increase from 3 to 34 hr post marathon with the runners' years of training.…”
Section: Discussionsupporting
confidence: 84%
“…The changes in plasma volume described here are relatively high compared to previous publications (11)(12)(13)(14)(15)9,16). These test groups were to some extent very heterogenous with respect to gender and level of training (14,17,9) or consisted of very few subjects e.g.…”
Section: Discussionmentioning
confidence: 52%
“…31 Schernthaner et al 32 found a 2-to 3-fold increase in β-thromboglobulin and PF4 levels after exercise. Placanica and colleagues 33 reported that patients with ischemic heart disease had high basal concentrations of PF4 and that these levels increased with exercise.…”
Section: Discussionmentioning
confidence: 98%
“…Also, based on one marathon study, despite increased levels of B-thromboglobulin, platelet aggregation was found to decrease after exercise (Rock et al, 1997). Platelet activation during exercise may be related to shear stress causing endothelial damage, increase in plasma thrombin generation, catecholamines and mobilezation of more active platelets from the reticuloendothelial system (Rocker et al, 1986). Based on the results presented in this study, it was observed that TT significantly increased on different tissues in EP rats after short and long times physical activity (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%